2019
DOI: 10.2147/cmar.s200684
|View full text |Cite
|
Sign up to set email alerts
|

<p>Development and validation of a nomogram to predict liver metastasis in patients with pancreatic ductal adenocarcinoma: a large cohort study</p>

Abstract: Background: Few studies have explored the relationship between clinicopathological factors of patients with pancreatic ductal adenocarcinoma (PDAC) and liver metastasis. The aim of this study was to develop and validate a nomogram to predict liver metastasis in patients with PDAC. Patients and methods: Patients diagnosed with PDAC between 2004 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database were retrospectively collected. The nomogram was establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…This result reveals that there are probably other metastases when liver metastases are found. This finding is consistent with other studies [ 23 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…This result reveals that there are probably other metastases when liver metastases are found. This finding is consistent with other studies [ 23 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…Study by Cai et al combined age, grade, histology, T stage, lymph node metastasis, and tumor size to predict the metastasis in T1 and T2 gallbladder cancer [ 17 ]. In pancreatic ductal adenocarcinoma, demographic and clinicopathological characteristics were used to construct nomogram to evaluate metastasis [ 18 ]. However, there is still no similar study in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…It may be caused by different hormone levels between male and female, which deserved to be confirmed by further molecular mechanism research. Several reports indicated that the tumor with larger size had the higher risk of distant metastasis [ 20 22 ]. Lymph node metastasis and higher pathological grades are important predictors for the survival of ICC patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%